Efforts To Prevent and Handle Cyberbullying in The School Environment - Sakiruddin Istiqomah , Risa; Zada, Mohd Ziaolhaq Qazi; Athiyallah, Arina (STAI Publisistik Thawalib Jakarta, 2024)
The use of the internet has triggered the rise of cyberbullying among adolescents, leading to severe emotional impacts. This study examines strategies for preventing and handling such threats in schools to protect students from such threats. The research method is a literature review, with data collection through documentation techniques. Data analysis is done through reduction, data presentation, and conclusion drawing. The research findings: To prevent cyberbullying, schools can implement awareness programs, integrate digital ethics into the curriculum, and offer teacher training. Open communication between schools, parents, and students is essential for identifying and addressing cyberbullying. Developing social skills, empathy, and conflict resolution also helps students manage online behavior, fostering a safer digital environment. Handling cyberbullying cases requires clear reporting procedures, thorough investigations, and fair sanctions. Schools should provide emotional support to victims and integrate anti-cyberbullying education. Teachers and staff must support victims while enforcing strict measures for perpetrators. Parents play a key role by supervising online activities, providing emotional support, and collaborating with schools to address and prevent cyberbullying effectively. Conclusion: Collaboration among schools, teachers, parents, and students is essential in preventing cyberbullying through emotional support, digital education, and reporting procedures.